Realization of the Principles and Purposes of Banking Activity in the System of Financial Monitoring in Russia - A. I. Andrianova (Путеводитель предпринимателя)
The article describes special characteristics of purposes and principles of banking activity as a form of economic activity in the connection between banking activity and financial monitoring in Russia (author means financial monitoring as a part of financial activity of the state). The study examined the object of our interest in the analysis of such features of the legal order of the financial monitoring in Russia as monitoring authority of banks, Central Bank of Russian Federation; connection between banking control and financial monitoring; exchange of information between Russian Service of Financial Monitoring, Central Bank of Russian Federation and other sections of bank system.